Ultrastructural morphologic description of the wild rice species Oryza latifolia (Poaceae) in Costa Rica - Ethel Sánchez; Mayra Montiel; Ana M. Espinoza (Revista de Biología Tropical, 2003)
The wild rice species Oryza latifolia is endemic to Tropical America, allotetraploid and has a CCDD genome type. It belongs to the officinalis group of the genus Oryza. This species is widely distributed through-out the lowlands of Costa Rica and it is found on different life zones, having great morphologic diversity. The purpose of this research is to perform a morphologic description of O. latifolia samples of three Costa Rican localities (Carara, Liberia and Cañas) and to see if the phenotypic diversity of the species is reflected at the ultra-structure level. Structures such as the leaf blade, ligule, auricles and spikelet were analyzed. Leaf blade morphology of the specimens from the three localities is characterized by the presence of diamond-shaped stomata with papillae, zipper-like rows of silica cells; a variety of evenly distributed epicuticular wax papillae and bulky prickle trichomes. The central vein of the leaf blade from the Cañas populations is glabrous, while those from Carara and Liberia have abundant papillae. There are also differences among the borders of the leaf blade between these locations. Cañas and Liberia present alternating large and small prickle trichomes ca. 81 and 150 µm, while Carara exhibits even sized prickle trichomes of ca. 93 µm. Auricles from Cañas are rectangular and present long trichomes along the surface ca. 1.5 mm, while those of Liberia and Carara wrap the culm and exhibit trichomes only in the borders. The ligule from the plants of Carara has an acute distal tip, while that of Cañas and Liberia is blunt. The Liberia spikelet has large lignified spines while Cañas and Carara show flexible trichomes. La especie silvestre Oryza latifolia es endémica de América, tetraploide y de genoma CCDD. Pertenece a las especies del género Oryza del grupo officinalis. Presenta una amplia distribución en las tierras bajas de Costa Rica y se le encuentra en varias zonas de vida, mostrando una gran diversidad morfológica. El propósito de este trabajo fue realizar una descripción ultraestructural de plantas de O. latifolia provenientes de las localidades Carara, Liberia y Cañas con el fin de determinar si hay variación intrapo-blacional. Se analizó la lámina foliar, lígula, aurículas y espiguilla, con énfasis en las estructuras de valor taxonómico. La morfología de la lámina foliar de los especímenes de las tres localidades se caracteriza por la presencia de estomas romboidales con papilas, células de sílice de forma crenada, variedad de papilas de cera, distribuidas en forma regular y tricomas espinosos abultados de ca 53 µm. La vena central de la lámina foliar de O. latifolia, localidad Cañas, es lisa, mientras que en Carara y Liberia presenta papilas. Los bordes de la lámina foliar difieren entre localidades; Cañas y Liberia presentan tricomas ganchudos grandes de ca. 150 µm y pequeños de ca 81 µm que alternan, mientras que Carara tiene tricomas ganchudos pequeños de igual tamaño (ca. 93 µm). Las aurículas de Cañas son rectangulares y presentan tricomas atenuados largos de ca. 1.5mm en toda la superficie, mientras las de Liberia y Carara son envolventes y presentan dichos tricomas solamente en los bordes. La lígula de Carara tiene el extremo distal agudo, mientras que Cañas y Liberia lo tienen truncado. La espiguilla de Liberia presenta tricomas espinosos lignificados grandes, mientras que Cañas y Carara tienen tricomas flexibles.